Optimized progression of Full-Body In-Bed Gym workout: an educational case report - Barbara Ravara; Walter Giuriati; Maria Chiara Maccarone; Helmut Kern; Stefano Masiero; Ugo Carraro (PAGEPress Publications, 2023)
People suffering from fatigue syndromes spend less time exercising each day, thus aggravating their motor difficulties. Indeed, muscles and mobility deteriorate with age, while exercising muscles is the only sure countermeasure. It is useful to offer a safe and toll-free rehabilitation training: Full-Body In-Bed Gym, easy to learn and performe at home. We suggest a 10-20 min daily routine of easy and safe physical exercises that may improve the main 200 skeletal muscles used for every-day activities. Many of the exercises can be performed in bed (Full-Body In-Bed Gym), so hospital patients can learn this light workout before leaving the hospital. The routine consists of series of repetitions of 15 bodyweight exercises to be performed one after the other without time breaks in between. Alternating sequences of arm and leg exercises are followed by moving body parts in lying and sitting positions in bed. These are followed by series of tiptoeing off the bed. Progressive improvements can be tested by a series of push-ups on the floor. Starting from 3-5, number of repetitions are increased by adding 3 more every week. To maintain or even shorten total daily time of workout each movement is weekly speeded up. The devoted time every morning (or at least five days a week) to train all the major muscles of the body can remain under 10 minutes. Because there are no breaks during and between sets, the final push-ups become very challenging: at the end of the daily workout heart rate, depth and number of ventilations and frontal perspiration increase for a few minutes. We here provide an example of how to implement the progression of the Full-Body In-Bed Gym presenting an educational Case Report of a trained 80-year old person in stable pharmacological managements. In addition to strengthening the main muscles, including the ventilatory muscles, Although performed in bed, Full-Body In-Bed Gym is a resistance training equivalent to a short jog.. Started in early winter and continued regularly throughout spring and summer, Full-Body In-Bed Gym can help maintain independence of frail people, including those younger persons suffering with the fatigue syndrome related to the viral infection of the recent COVID-19 pandemic.